Research in the history of economic thought and methodology a research annual. Vol. 30, part 1 - Biddle, Jeff; Emmett, Ross B. (Research in the history of economic thought and methodology., 2012)
The collection includes both refereed articles and review essays of recently published books in the history of economic thought and methodology. The articles highlight the work of founding editor Warren J. Samuels, American economists role in the creation of federal trade acts, and Islamic economic methodology. A review symposium on Malcolm Rutherfords The Insitutionalist Movement in America is followed by reviews of books on Adam Smith, George Warde Norman, William Whewell and Richard Jones, J.S. Mill and F.A. Hayek.